An exploratory study on differences in cumulative plantar tissue stress between healing and non-healing plantar neuropathic diabetic foot ulcers. (March 2018) - van Netten, Jaap J.; van Baal, Jeff G.; Bril, Adriaan; Wissink, Marieke; Bus, Sicco A.
Abstract: Background: Mechanical stress is important in causing and healing plantar diabetic foot ulcers, but almost always studied as peak pressure only. Measuring cumulative plantar tissue stress combines plantar pressure and ambulatory activity, and better defines the load on ulcers. Our aim was to explore differences in cumulative plantar tissue stress between people with healing and non-healing plantar diabetic foot ulcers. Methods: We analyzed a subgroup of 31 patients from a randomized clinical trial, treated with a removable offloading device for their plantar diabetic forefoot ulcer. We measured in-device dynamic plantar pressure and daily stride count to calculate cumulative plantar tissue stress at the ulcer location and associated this with ulcer healing and ulcer surface area reduction at four weeks (Student's t and chi-square test for significance, Cohen's d for effect size). Findings: In 12 weeks, 68% ( n  = 21) of the ulcers healed and 32% ( n  = 10) did not. No statistically significant differences were found for cumulative plantar tissue stress, plantar pressure or ambulatory activity between people with healed and not-healed ulcers. Cumulative plantar tissue stress was 25% lower for people with healed ulcers (155 vs. 207 MPa·s/day; P  = 0.71; Effect size: d  = 0.29). Post-hoc analyses in the 27 patients who self-reported to be adherent to wearing the device showed that cumulative plantar tissue stress was 49% lower for those who reached ≥75% ulcer surface area reduction at four weeks (140 vs. 275 MPa·s/day; P  = 0.09; d  = 0.76); smaller differences and effect sizes were found for peak pressure (24%), peak pressure-time integral (30%) and ambulatory activity (26%); ( P -value range: 0.14–0.97; Cohen's d range: 0.14–0.70). Interpretation: Measuring cumulative plantar tissue stress may provide insight beyond that obtained from plantar pressure or ambulatory activity alone, with regard to diabetic foot ulcer healing using removable offloading devices. These explorative findings provide baseline data for further studies on this relevant topic. Highlights: Cumulative tissue stress was 25% lower in healed plantar diabetic foot ulcers. This effect was 49% in adherent patients. Plantar pressure or ambulatory activity alone resulted in smaller differences. Measuring cumulative tissue stress may provide insight beyond pressure or activity.